The Analysis of Role of Motivation, Career Development and Compensation on Performance of Vocational High School Teachers - Agus Siswanto; Zunan Setiawan; Rivaldo Kurniawan Iryanto; Zainiyatul Afifah; Abdurohim Abdurohim (Journal on Education, 2023)
The purpose of this study is to ascertain how motivation, pay, and career advancement affect teachers' performance. The study's sample consisted of 51 teachers. Multiple regression is the statistical tool utilized, with the sample method being simple random sampling. Using the statistical program SPSS 16.0, data were examined. With a sig F value of 0.000 < 0.1 and an f-count of 18.976, the findings of this study demonstrate that motivation, compensation, and career growth strongly influence teacher performance. The findings of the motivation t-test, with a sig t value of 0.025 < 0.1 and a t-count value of 2.310, have a significant impact on teachers' performance. With a significant value of 0.000 < 0.1 and a t-count of 4.439, career growth strongly influences teacher performance.